Delayed Valsalva obstruction after transcatheter self-expandable aortic valve implantation: a case report. Issue 6 (13th December 2020) - Ohya, Masanobu; Fuku, Yasushi; Shimamoto, Takeshi; Kadota, Kazushige
Abstract: Background: Delayed coronary obstruction after transcatheter aortic valve implantation has been reported to occur more commonly after self-expandable aortic valve implantation than balloon-expandable valve. Case summary : An 86-year-old woman treated by transcatheter self-expandable aortic valve implantation had acute coronary syndrome 3 months after the procedure. Emergent coronary angiography showed decreased blood flow in the left coronary artery. Balloon angioplasty between the valve frame and the left coronary cusp was performed, and her ischaemia resolved. Contrast-enhanced computed tomography showed a commissural post of the supra-annular valve overlying the left coronary cusp, and serial computed tomography showed the valve frame expanding over time. She received coronary bypass grafting using saphenous vein grafts for the left anterior descending and left circumflex arteries. Four months after surgery for the left anterior descending artery, the patient had recurrent chest pain, and computed tomography showed a graft occlusion in the left anterior descending artery. Shortly afterwards, she died of sudden cardiac arrest. Discussion : In this report, we describe delayed Valsalva obstruction after transcatheter self-expandable aortic valve implantation, which can be detectable by serial computed tomography. The sealing of a coronary cusp by a commissural post of the valve may be one of the causes of delayed coronary ischaemia after transcatheter self-expandable aortic valve implantation.